PENCIPTAAN KARYA TARI SLENDANG PEMALANG SEBAGAI TARI IDENTITAS KABUPATEN PEMALANG - Evi Septimardiati (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2013)
The Slendang Pemalang dance was created by Koestoro in 1985. It is a form of social dance which may be performed asa solo, a duet, or by a group, and uses a scarf or slendang that is tied and used in various ways. The Slendang Pemalangdance was declared a form of regional identity in a decree by the Regent of this area on 17 September 2012. The localPemalang government subsequently adopted this dance as a form to promote its regional identity. This decision is proof thata system has the power to undertake, control, arrange, and preserve the potential expression of its regional art which isintegrated in a symbolic process. This system connects the artist, the Regent, the local government, the tourist board, and thePemalang community in a system of values of its regional identity. The performance of dance at certain ceremonies is used asa tool to display authority. The style of a dance performance as a protocolary substance and ceremony involving the Regentis a form of imaging that is used as a means of increasing the level of authority.Keywords: social dance, Pemalang identity